Determination of the Concentration of Radionuclide in Tomato samples collected from The North-East Region of Libya - Saeid Y. Elorfi , Marai M. Imsallim (Journal of Pure & Applied Sciences, 2018)
The radio isotopic analysis of vegetation is vital. It acts as a tool in indicating contaminated vegetables which are consumed by humans on a daily basis. Hence isotopic analysis has become of interest worldwide including Libya.This work aims at measurement and evaluation of activity concentrations of radionuclides in tomato and corresponding soil samples in the north east region of Libya. The concentration of radionuclides in the soil and tomato samples was measured using gamma spectroscopy described below. The radioactive analysis of soil shows the average activity concentration of 40K, 238U and 232Th series, and 137Cs in soil are , ,  and  dry weight respectively. The radioactive analysis of tomato samples showed that 40K is the only radionuclide detected with an average of  dry weight. The average radionuclide concentration ratio (C.R.) of 40K for tomato is